The export-magnification effect of offshoring - Jörn Kleinert; Nico Zorell (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2010)
In this paper we argue that the surge in world trade over the two decades preceding the global downturn of 2008-09 can be partly explained by the export-magnification effect of offshoring. In a general equilibrium model with heterogeneous firms we show analytically that a fall in variable offshoring costs boosts trade in differentiated final goods through an intra-industry reallocation of resources towards the more productive firms. More specifically, lower barriers to offshoring reduce the input costs of incumbent offshoring firms and allow more firms to source cheap foreign intermediates, which improves firm-level price competitiveness. This, in turn, translates into higher export quantities of incumbent exporters (intensive margin) and entry of new exporters (extensive margin), thereby fostering trade in final goods.
urn:nbn:de:bsz:21-opus-53294
Keywords: F12; F23; 330; Offshoring; trade; multinational firms